Comparing the Effectiveness of the Mindfulness-Based Stress Reduction Program and Cognitive-Behavioral Therapy on Pain Severity and Alexithymia in Women with Fibromyalgia - Aziminia, Rezvaneh; Azadi, Mehran; Sedaghat, Mastooreh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of the Mindfulness-Based Stress Reduction (MBSR) program and Cognitive-Behavioral Therapy (CBT) on pain severity and alexithymia in women diagnosed with fibromyalgia. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest and follow-up structure including a control group. The statistical population consisted of women diagnosed with fibromyalgia who attended the rheumatology clinic of Sina Hospital in Tehran between August and October 2025. From this population, 45 participants were selected through purposive sampling and randomly assigned to three groups: Mindfulness-Based Stress Reduction (n = 15), Cognitive-Behavioral Therapy (n = 15), and control (n = 15). The experimental groups received eight weekly intervention sessions, while the control group received no intervention. Data collection instruments included the McGill Pain Questionnaire and the Toronto Alexithymia Scale (TAS-20). Data were analyzed using multivariate analysis of variance (MANOVA) and Bonferroni post hoc tests in IBM SPSS Statistics version 21. Findings: The results of multivariate analysis of variance indicated significant differences among the study groups in all dimensions of alexithymia and pain severity at the posttest stage (p < .001). Significant effects were observed for difficulty identifying feelings, F = 181.32, difficulty describing feelings, F = 184.71, externally oriented thinking, F = 49.02, affective pain perception, F = 120.88, sensory pain perception, F = 63.81, evaluative pain perception, F = 44.82, and total pain severity, F = 40.45. Bonferroni post hoc comparisons demonstrated that both MBSR and CBT significantly reduced alexithymia and pain severity compared with the control group (p < .001). Moreover, the MBSR group showed significantly greater reductions in total pain severity and emotional dysfunction compared with the CBT group. Conclusion: Both Mindfulness-Based Stress Reduction and Cognitive-Behavioral Therapy were effective in reducing pain severity and alexithymia among women with fibromyalgia. However, the mindfulness-based intervention demonstrated greater effectiveness in improving emotional regulation and reducing pain-related symptoms.